Mauriac Syndrome in a Child with a Positive Antinuclear Antibody Screen - John F. Pohl (Gastroenterology Research and Practice)
A 17-year-old male with type 1 diabetes mellitus (T1DM) presented to clinic with elevated transaminases and a positive antinuclear antibody (ANA) screen. Due to concern for autoimmune hepatitis, a liver biopsy was performed which revealed Mauriac syndrome. This case report is the second known description of a child with Mauriac syndrome presenting with positive autoimmune markers.